2019
DOI: 10.1080/09645292.2019.1565401
|View full text |Cite
|
Sign up to set email alerts
|

Day care quality and changes in the home learning environment of children

Abstract: Children's development is fostered by both high quality Early Childhood Education and Care (ECEC) settings and high quality home learning environments. As we know little about the interrelations between these two environments, we examine whether the child's attendance in a high quality ECEC arrangement relates to the quality of her home learning environment. Using rich NICHD Study of Early Child Care and Youth Development data, we show that ECEC quality is associated with the home learning environment, even af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…The echoes of school experiences at home showed that children had inadequate stimulation, limited interactions with their parents and poor enrichment at home. While this was an expected result, it is a significant contribution to the limited literature on school-home connections for disadvantaged children (Kuger, Marcus, & Spiess, 2019). Increasing the number of quality activities and involving families in education through using culturally relevant practices may contribute to disadvantaged children's home life and future success in elementary school.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 76%
“…The echoes of school experiences at home showed that children had inadequate stimulation, limited interactions with their parents and poor enrichment at home. While this was an expected result, it is a significant contribution to the limited literature on school-home connections for disadvantaged children (Kuger, Marcus, & Spiess, 2019). Increasing the number of quality activities and involving families in education through using culturally relevant practices may contribute to disadvantaged children's home life and future success in elementary school.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 76%
“…through teacher recommendations (see e.g. Cornelissen et al, 2018;Kuger et al, 2019). 9 Moreover, if center-based care has a direct effect on children's cognitive or socio-emotional development, parents could adjust their inputs in response to this and increase their time spent on specific parenting activities (see Nicoletti and Tonei, 2020).…”
Section: Indirect Effectsmentioning
confidence: 99%
“…One of the few economic studies not to take the home environment as given isKuger et al (2019), which shows that the quality of center-based care affects the quality of the home environment, using established quality measures for both environments.4 Our analysis is restricted to families with one child below the age of ten for data reasons. Using a household survey, we show in a complementary analysis in appendix C.2 that when we contrast results with and without the same sample restriction they hardly differ.5 Interestingly, some studies focusing on the impact of maternal employment on parenting activities show that parental quality time with children does not need to decline with increases in maternal employment (e.g Bono et al, 2016 andBastian andLochner, 2020)…”
mentioning
confidence: 99%
“…Further, parent–child interactions during a variety of learning opportunities within and out of the home, such as singing songs to the child, rhyming, and visiting cultural places (e.g., Bradley and Caldwell, 1984 ; Melhuish et al, 2008 ), and the quality of interactions during play or shared reading are considered important aspects of the HLE (e.g., Son and Morrison, 2010 ; Linberg, 2018 ; Tamis-LeMonda et al, 2019 ; Lehrl et al, 2020a ). Although many research studies currently conceptualize the HLE domain-specifically according to the home literacy and/or numeracy model into aspects that capture formal and informal stimulation of language, literacy, and mathematics (e.g., Sénéchal and LeFevre, 2002 ; Manolitsis et al, 2013 ; Skwarchuk et al, 2014 ; Niklas et al, 2016 ; Lehrl et al, 2020a ), there are also numerous studies that combine the different facets of the HLE into one indicator to capture the overall stimulation of the HLE (e.g., Melhuish et al, 2008 ; Son and Morrison, 2010 ; Niklas and Schneider, 2017 ; Kuger et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%